Determinants of Productivity and Structural Change in a Large Commercial Farm Environment : Evidence from Ukraine - Deininger, Klaus; Nizalov, Denys; Singh, Sudhir K. (Published by Oxford University Press on behalf of the World Bank, 2019)
The coincidence of productivity improvements and growth of agriholdings in Ukraine over the last decade is often interpreted as evidence of technology-induced increasing returns to scale and superiority of very large farms. Panel data for the country’s commercial farms in 2001–2012 do not allow us to reject the hypothesis of constant returns to scale but point toward the importance of farms and rayon- (district) fixed effects. This suggests productivity growth was driven by exit of unproductive and entry of more efficient farms. Higher initial shares of area under farms above 3,000 or 5,000 ha at rayon level significantly reduce subsequent exit, pointing towards one channel through which land concentration may reduce productivity growth.